SIMULATION DIGITAL L OGIC AND THE IMPLEMENTATION OF OPERATION TRUTH BOOLEAN ALGEBRA ELECTRICITY USING NEURAL FREEWARE 1:01 - Ahmad Saugi; Fivtatianti Hendajani, SKom, MM (Jurnal Sistem Komputer, 2005)
Although the technology used to implement a digital system has fundamentally changed, but the basic principles of logic design has not changed. Truth table and table statement is still used to determine t he behavior of logic networks. Therefore, this paper aims to prove that in one or several logic circuit that is felt in the operating logic and the use or functionality of the operating principles of digital logic (binary) and apply Boolean algebra equatio ns. At this writing, proof of correct operation of digital logic and boolean algebra implementation proved by simulation of a series of switches and lights. And simulated with electrical nerve 1:01 freeware applications. so that can know the truth value ofÂ  simulation testing in accordance with the existing theoretical basis.